ASSESSMENT ANALYSIS OF THE CONDITION OF THE SEI. LALAK II BRIDGE USES FRACTURE CRITICAL MEMBER - Widya Apriani; Setiawan; Virgo Trisep Haris (Jurnal Infrastruktur, 2022)
Bridge inspection plays a vital role in prevention before the occurrence of continuous damage. Sei Bridge. Lalak II is a steel truss bridge located in the Airmolek Subdistrict, Indragiri Hulu Regency, Riau Province. The purpose of this study was to analyze the condition of the damage to the elements of the Sei bridge. Lalak II in Indragiri Hulu Regency. The method used to analyze the condition of bridge damage is based on the Fracture Critical Member (FCM) method While the results of the FCM method are trusses that have the highest stress ratio in rod number 2 with a stress ratio value (0.717), rod number 7 with a stress ratio value (0.717) and rod number 33 with a stress ratio value (0.717). From this value, the condition of the truss is in the warning category, so light rehabilitation is needed, such as painting the steel frame. At the FCM screening stage, the score obtained is 25 points, then the next examination is carried out for a maximum of the next 24 months. At the FCM assessment stage, the score obtained is 104 points, then the subsequent examination will be carried out in the next 12 months. The overall condition of the Sei bridge. Lalak II required light rehabilitation to maintain the bridge in the long term.